2013
DOI: 10.4187/respcare.02344
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Acute Care Patients Weaning From Prolonged Mechanical Ventilation Maintain Circadian Rhythm

Abstract: BACKGROUND Circadian rhythm regulates many physiologic and immunologic processes. Disruption of these processes has been demonstrated in acutely ill, mechanically ventilated patients in the ICU setting. Light has not been studied as an entraining stimulus in the chronically mechanically ventilated patient. The purpose of this study was to determine the association of naturally occurring ambient light levels in a long-term acute care (LTAC) hospital with circadian rhythm in patients recovering from critical ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…14-17 Three studies used accelerometry to measure physical activity and movement as surrogates for adequacy of sedation, 18-20 and 2 studies used accelerometry as a surrogate for measuring sleep/wake cycles. 21,22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14-17 Three studies used accelerometry to measure physical activity and movement as surrogates for adequacy of sedation, 18-20 and 2 studies used accelerometry as a surrogate for measuring sleep/wake cycles. 21,22 …”
Section: Resultsmentioning
confidence: 99%
“…The last 2 studies by Koldobskiy et al 21 and van der Kooi et al 22 used accelerometry as a surrogate for measuring sleep/wake cycles. Both studies evaluated accelerometry in clinically distinct populations: post-acute, ventilator-dependent subjects 21 and acutely ill, postoperative cardiac surgery subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observational study Koldobskyi et al have shown that specific facilities (like LTAC's) maintain the patients' circadian rhythm compared to the ICU environment. 35 In a recent meta-analysis, examining three trials involving a heterogeneous group of patients, inspiratory muscle training was found to significantly increase inspiratory muscle strength in adults undergoing mechanical ventilation. 36 Further research is needed including more homogeneous PMV populations and analyzing more relevant outcomes.…”
Section: Evidence-based Multidisciplinary Rehabilitative Interventionsmentioning
confidence: 98%
“…Cognitive rehabilitation 8,33,34 Feeding/nutrition and swallowing NA Sleep 35 Respiratory ---respiratory muscle training Secretion management; Weaning/decannulation protocols 36 37 38,39 Physical therapy ---limb exercises, exercise training, neuromuscular electrical stimulation See Table 1 Co-morbidities management (e.g. CHF, DM, COPD), Multidisciplinary rehabilitation in ventilator-dependent patients: Call for action in specialized inpatient facilities 5 Table 5 Members of the team and roles.…”
Section: Evidence-based Multidisciplinary Rehabilitative Interventionsmentioning
confidence: 99%